SAUNA APPARATUS - TEI REIHI (2020)
To acquire a sauna effect according to individual differences of subjects, and body conditions and recovery from a disease/progression of a disease on the same subject.SOLUTION: A sauna apparatus includes: heaters 400A-400D for heating a subject; heart rate-and-the-like sensors 840A and 840B for measuring heart rate information or pulse rate information on the subject; and controllers 800A and 800B for outputting a control signal for controlling heat quantity of 400A-400D and ON time of 400A-400D based on the information measured by the heart rate-and-the-like sensors 840A and 840B.SELECTED DRAWING: Figure 1 【課題】被験者らの個体差、同じ被験者でも体調や病状の回復／進行具合に応じたサウナ効果が得られるようにする。【解決手段】被験者を加温するヒータ４００Ａ〜４００Ｄと、前記被験者の心拍数情報又は脈拍数情報を計測する心拍数等センサ８４０Ａ，８４０Ｂと、心拍数等センサ８４０Ａ，８４０Ｂによって計測された情報に基づいて４００Ａ〜４００Ｄの熱量と４００Ａ〜４００Ｄのオン時間とを制御する制御信号を出力するコントローラ８００Ａ，８００Ｂと、を備える、サウナ装置。【選択図】 図１